TRANSFORMATIVE ADJUDICATION AND THE PLACE OF ADMINISTRATIVE LAW IN SOUTH AFRICAN JURISPRUDENCE: ABSA BANK LIMITED v PUBLIC PROTECTOR (The Pretoria Student Law Review, 2021)
The primary purpose of administrative law is to regulate the exercise of public power and the performance of public functions, which is informed by the constitutional principle of the rule of law.1 This paper argues that what underlies this objective in post-1994 mainstream transformation jurisprudence is a transformative approach in interpreting the Constitution,2 by which all exercises of power must be justified, including judicial interpretations.3 Klare coined this approach as ‘transformative constitutionalism’.4 This paper critically examines the decision in Absa Bank and Others v The Public Protector and Others (Absa case)5 concerning the High Court’s approach to adjudication in the administrative law and the role of a transformative constitutionalist approach to adjudication. The first part of this paper contains a brief exposition of the place of administrative law in the South African legal regime. In the second part of the paper, we provide a summary of the Absa case. We then provide a focussed discussion on procedural fairness as a cornerstone of good governance with respect to administrative conduct in the third section of the paper. The fourth part of the paper sets out what a transformative approach to adjudication is, including a discussion on how the Court in Absa dealt with the standard of fairness in relation to the Public Protector’s conduct from a transformative constitutionalist lens, on the one hand, and a critique on the Court’s application of the established principles of administrative law, on the other hand. Lastly, we conclude with recommendations in response to the Court’s seemingly split approach to transformative adjudication.
Keywords: administrative law; ‘transformative constitutionalism’; Absa Bank and Others v The Public Protector and Others; procedural fairness; transformative adjudication